Re-placing the Mediterranean Diet: Historical Exchanges and Possible Futures - Vitullo, Juliann; Melkozernova, Arina (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2024)
The term Mediterranean Diet (MedDiet) suggests a strong geographic orientation, a connection to a region—its flora, fauna, land, sea and histories–that its current generic and ephemeral classification (2018-2023) as the “the best diet overall” by the U.S. World and News Report ignores. As this consistent ranking suggests, one of the most common representations of the “Mediterranean” today, in the U.S., and even globally, is that of the MedDiet. It is a concept, tied to idealized images of health and pleasure, which first developed through exchanges in the post-WWII period between scientists from the United States and communities in Greece and southern Italy, which had not yet been substantially transformed by industrialized agriculture and highly processed foods. In the 1950’s the now-famous physiologist from the U.S., Ancel Keys, “discovered” the MedDiet during a research trip to Naples. Ever since, tension has existed between Keys’s place-based research and the call for this diet, based largely on plant foods, seafood, olive oil, and limited consumption of meat and dairy products, to be universally translated. Any attempt to evaluate the influence of the MedDiet must face the overwhelming influence of the model in scientific studies (with over 5,000 publications a year just since 2020 in the U.S.) as well as its branding by agri-food interests. While Ancel Keys’s epidemiological research on lipids and heart disease was groundbreaking, the concept of the MedDiet has evolved into a global scientific mythology that needs to be reevaluated and re-placed into specific historical and social contexts that acknowledge the biological and cultural diversity of Indigenous, peasant, and traditional foodways as well as the challenges of the contemporary industrialized food system. As early as 1998, two southern Italian researchers, Vito Teti and Massimo Cresta, formed a transdisciplinary team that questioned the tunnel vision of the scientific model, reminding scholars that the southern Italian communities associated with the MedDiet had evolved agricultural and eating patterns, which maintained balanced and sustainable relationships, not as a choice but as a means of survival in specific environments. Although their research has been largely ignored by scholars of the MedDiet, it invites us to examine how certain traditional Italian foodways were de-territorialized or stripped of their rich and complex cultural and environmental histories, as scientists paradoxically categorized them using the often-slippery geographical term of “Mediterranean.” At the same time, the contemporary revalorization of the biocultural heritage created over generations within marginalized communities in southern Italy, which Vito Teti continues to help document through his concept of la restanza, emphasizes the importance of recognizing transdisciplinary and transnational exchanges as well as the possibility of healthier and more sustainable futures through relational and collaborative foodways wherever we live.